Identification of microtubule-associated proteins in the centrosome, spindle, and kinetochore of the early Drosophila embryo (The Rockefeller University Press, 1989)
We have developed affinity chromatography methods for the isolation of microtubule-associated proteins (MAPs) from soluble cytoplasmic extracts and have used them to analyze the cytoskeleton of the early Drosophila embryo. More than 50 Drosophila embryo proteins bind to microtubule affinity columns. To begin to characterize these proteins, we have generated individual mouse polyclonal antibodies that specifically recognize 24 of them. As judged by immunofluorescence, some of the antigens localize to the mitotic spindle in the early Drosophila embryo, while others are present in centrosomes, kinetochores, subsets of microtubules, or a combination of these structures. Since 20 of the 24 antibodies stain microtubule structures, it is likely that most of the proteins that bind to our columns are associated with microtubules in vivo. Very few MAPS seem to be identically localized in the cell, indicating that the microtubule cytoskeleton is remarkably complex.